The impact of environmental factors on bank efficiency: A parametric analysis of Hong Kong banking sector - Deng, Wenyang (2012)
This paper examines the X-efficiency of Hong Kong banks cover the period of year 2006 to 2011. The goal of this analysis is to identify the impacts brought by environmental variables on Hong Kong banking’s efficiency, especially the tighter business cooperation between Hong Kong and Mainland China and 2008 sub-prime financial crisis erupted in USA. To conduct this analysis, a stochastic input distance function is utilized and a two-stage research structure is constructed. Results show that the Hong Kong banking efficiency has a gradually declined tendency before or after incorporating the environmental variables. Before incorporating the environmental variables, Hong Kong banks’ average X-efficiency scores lie in the range of 0.71 to 0.92 from year 2006 to year 2011. In addition, bank size, measured by banks’ total deflated asset, has different impacts on banks on different level. Large size banks have similar X efficiency tendency with small size banks. And their average X-efficiency scores are all higher than medium size banks. Hong Kong banks’ X-efficiency scores could also differ under different consolidation status. Generally, consolidated banks enjoy higher X-efficiency scores than unconsolidated banks. After incorporating the environmental variables, X-efficiency scores for Hong Kong banking sector has become more converged, with a lowest score of 0.79 and a highest score of 0.87. The similar change can also be applied in studying the topics of either bank size and X-efficiency, or consolidation status and X-efficiency, which confirms that environmental variables are found to make marked difference on Hong Kong banking efficiency evaluation. In other words, failure to incorporate the environmental factors may not be able to adequately describe the Hong Kong banking efficiency tendency for the past six years.